Ação para sustentabilidade: análise de viabilidade para implantação de usina para tratamento de resíduos sólidos urbanos com recuperação energética. - Oliveira, José Henrique de (2016)
This study presents a proposal for the specification of a software for municipal solid waste management, energy recovery and economic-financial viability analysis for the implementation of a municipal solid waste incineration plant for municipal consortia as demonstrative of the features expected for this software. Although the national solid waste policy advocates the use of landfills for the disposal of solid waste from urban areas, this solution presents various environmental impacts such as greenhouse gas emissions and the production of toxic effluents arising from the decomposition process of residues. The incineration and recycling are already the main waste treatment methods in developed countries, while in Brazil, recycling is restricted to a few initiatives and incineration is used only for treatment of industrial waste and waste of health services. Whereas all municipalities should abandon the practice of depositing their waste in landfills and considering such practice the most common in small towns, the move to more environmentally friendly practices will result in continuous financial expenditures, since all landfills have a limited life expectancy. Therefore, incineration can be a viable alternative to increase the life expectancy of landfills, provides an extra source of revenue for the production of electricity and the sale of carbon credits. Thus, this study aims to analyze the economic-financial feasibility of implementing a power plant generation from the incineration of municipal solid waste for different population groups and propose a specification of a software for this type of analysis. For feasibility analysis and software specification, production data was raised from municipal solid waste in the region of Foz do Iguaçu-PR, in the municipalities of the region and the concessionaires of collection services, as well as in municipal transparency portals in electronic site of the Ministry of Mines and Energy and other relevant electronic sites. After collecting data, it was carried out a qualitative analysis of the requirements for the software specification and a quantitative analysis to empirically determine the economic fea sibility of deployment of a waste incineration plant. In addition to presenting the software specification for management and analysis of environmental projects, it was verified the economic and financial viability of the implementation of a solid waste incineration plant in the region of Foz do Iguassu - PR.